Total factor productivitygrowth in Indian manufacturing: New Evidences using Data Envelopment Analysis (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The present paper evaluates the performances of manufacturing industries withrespect to total factor productivity. TFP changesand its components are estimated for68 three-digit manufacturing industries for the period from 2008-09 to 2017-18 usingdata from Annual Survey of Industry (ASI) by employingMalmquist ProductivityIndex based data envelopment analysis. The study uses gross value added basedsingle deflation method as output using 2011-12 as a base period. Capital stock andlabour are used as inputs. The paper uses Perpetual Inventory Method to derive themeasure of capital input series. It was found that the year 2015-16 has reportedhighest TFP growth mainly due to technological changes. All the study periodexhibits positive trend in TFP growth.In the case of industry-wise analysis, the studyalso found that the TFP growth is highest in the manufacturer of magnetic and opticalmedia followed by manufacturer of jewelry and related articles. It is evident form theresult that the increase in TFP growth is due to technological changes and decrease inTFP growth is due to technical efficiency change.